543. 432:545. 82:546. 562 APPLICATION OF 1-(2-HYDROXY-1-NAPHTOAZO)-2-NAPHTHOL-4- SULFO ACID IN AMPEROMETRIC DETERMINATION OF SCANDIUM ION - TURSUNQULOV, JASUR; QUTLIMUROTOVA, NIGORA (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Scandium metal is widely used in the production of heat-resistant, corrosion-resistant optical objects, in the production of expensive instruments in industry and medicine. The article is devoted to the detection of scandium ion using 1-(2-hydroxy-1-naphthoazo)-2-naphthol-4-sulfo acid on natural objects by electrochemical method. Optimum conditions for amperometric determination of scandium with 1-(2-hydroxy-1-naphthazo)-2-naphthol-4-sulfonic acid: at pH 2.58, voltage 0.6 V, reaction speed 3.7 seconds, participating 4 number of electrons on the electrode surface, and the Me:R ratio is 1:1 is found. Yb 3+ , Cd 2+ , Pb 2+ , Fe 2+ cations in a 1:1 mol ratio were found not to affect the determination of scandium. The accuracy of the developed method was 99.99 when using technological water analysis in the process of gold mining.